PENGARUH PENYULUHAN GIZI DENGAN MEDIA GAME EDUKASI BERBASIS ANDROID TERHADAP KONSUMSI BUAH DAN SAYUR - Purba, Jonni Syah R.; Nopriantini, Nopriantini; Rafiony, Ayu; Petrika, Yanuarti (Poltekkes Kemenkes Bandung, 2024)
The main issue faced in fruit and vegetable consumption is that, on a national scale, the consumption of fruits and vegetables by the Indonesian population is still below the recommended levels. In the context of increasing needs for nutritional and health understanding, this study aimed to examine the effect of an android-based educational game on fruit and vegetable consumption through teacher capacity enhancement among junior high school students in Ngabang, Landak Regency. A quasi-experimental method utilizing the separate sample pretest-posttest control group design was employed with two treatment groups. The sample consisted of 35 Grade 8 students for each group. The sampling technique used quota sampling. Statistical analysis using paired t-test and independent t-test. The results indicate there was no significant difference in fruit consumption frequency between the control group before and after the intervention (p=0.160), whereas a significant difference was observed in the treatment group (p=0.000). Similar patterns were observed for vegetable consumption frequency, with no difference in the control group (p=0.263) but a significant difference in the treatment group (p=0.000). Overall, the study found a significant difference in the frequency of consumption between the control and treatment groups for both fruits (p=0.000) and vegetables (p=0.000). This suggests that the android-based educational game, through enhancing teacher capacity, effectively increases fruit and vegetable consumption among junior high school students. These findings highlight the potential of using educational technology to improve dietary habits and address nutritional issues among adolescents in Indonesia.